Virtuality of hybrid design teams within the construction context: A conceptual model - Hosseini, M.; Chileshe, N.; Baroudi, B.; Izadpanahi, Parisa; Zuo, J. (Inderscience Publishers, 2017)
Copyright © 2017 Inderscience Enterprises Ltd.Construction managers are required to harness the benefits of hybrid design teams in which interactions are increasingly both virtual and face-to-face. In this context, virtuality plays a crucial role in hybrid teams. This has made a comprehensive appreciation of the nature of virtuality very relevant within the construction context. That is because, virtuality is a key determinant within the design and best practices for adopting hybrid design teams within construction organisations. Yet, a review of literature reveals a conspicuous absence of studies on virtuality within construction. To address this, as a first enquiry targeting virtuality in the construction context, the study synthesises the existing literature and encapsulates available knowledge in a conceptual model describing virtuality for hybrid design teams within construction. It is put forth that such a conceptual model will further establish the field, and can provide fertile ground for future empirical studies on hybrid design teams in the construction context.